Selection of welding robot by multi-criteria decision-making method - Son, Nguyen Hong; Hieu, Tran Trung (Eastern-European Journal of Enterprise Technologies, 2023)
Welding is a method to join parts together by a stable connection. Welding is used in many different fields. The limitations of manual welding methods are gradually eliminated when using welding robots. The selection of a welding robot has a great influence on the efficiency of the welding process. Choosers (customers) often encounter problems when choosing among many products that are available in the market. During this study, seven types of robots were given to make a choice including AR700, AR900, AR1440, AR1730, AR2010, MA3120, VA1400 II. These seven options are commonly used in welding processes. There are a variety of different parameters (criteria) used to evaluate each of these robots. However, the value of the criteria in the robots is very different. The selection of a robot that is considered the best should be based on all those criteria. At this point, the selection of robots is called MCDM (Multi-Criteria Decision-Making). In this research, two MCDM methods were used to rank the types of robots: MARCOS (Measurement of Alternatives and Ranking according to COmpromise Solution) and PSI (Preference Selection Index). The determination of important quantities for the criteria has been carried out by various methods, including the MEREC (MEthod based on the Removal Effects of Criteria), EQUAL, ROC (Rank Order Centroid) and RS (Rank Sum) methods. The MARCOS method was used four times corresponding to four different sets of weights. Meanwhile, when using the PSI method, we do not need to calculate the weights for the criteria. All five ranking results indicate the same best alternative. The results indicate that MA3120 is the best one. The two methods MARCOS and PSI are reliable enough to be used when multi-criteria decision-making is required, firstly, in the selection of welding robots.